Diagnostic costs: a research in a family medicine outpatient clinic - Sahin, Safiye; Esen, Fevzi; Zeren Ozturk, Guzin (Acta Scientiarum. Health Sciences, 2022)
The aim of this study is to evaluate the direct diagnostic costs for disease groups and other variables (such as gender, age, seasons) that are related to the direct diagnostic costs based on a 3-year data. The population of the study consisted of 31,401 patients who applied to family medicine outpatient clinic in Turkey between January 1st, 2016 and December 31st, 2018. With this study, we determined in which disease groups of the family medicine outpatient clinic were most frequently admitted. Then, total and average diagnostic costs for these disease groups were calculated. Three-year data gave us the opportunity to examine the trend in diagnostic costs. Based on this, we demonstrated which diseases’ total and average diagnostic costs increased or decreased during 3 years. Moreover, we examined how diagnostic costs showed a trend in both Turkish liras and USA dollars’ rate for 3 years. Finally, we analysed whether the diagnostic costs differed according to variables such as age, gender and season. There has been relatively little analysis on the diagnostic costs in the previous literature. Therefore, we expect to contribute to both theorists and healthcare managers for diagnostic costs with this study.